Association between anxiety and depression in Medical students at Universidad Ricardo Palma during the year 2021: Asociación entre ansiedad y depresión en estudiantes de Medicina de la Universidad Ricardo Palma durante el año 2021 - Nina, Mashiel Leiva (2022)
The mental health of medical students around the world has been affected by the presence of anxiety and depression. According to the World Health Organization, more than 260 million people suffer from anxiety and approximately 300 million people suffer from depression. Objective: To determine the association between anxiety and depression in medical students at Ricardo Palma University during the 2021-II academic year. Materials and Methods: Observational, analytical, cross-sectional and quantitative study. From a population of 2046 medical students from the first to the seventh year of studies, the size of the sample obtained was 110 students. The data obtained was collected through Google Forms. Results: Of the medical students, 85.46% manifested some degree of anxiety and 50% manifested some degree of depression. These pathologies occurred more frequently in the female sex, low socioeconomic level and in those who had clinical courses. A statistically significant association was found between anxiety and depression (p: 0.038), and between low socioeconomic status and depression (p: 0.004). No statistically significant association was found between female sex and depression, nor between pre-clinical courses and depression. Conclusions: High prevalences of anxiety and depression were found in medical students at the Ricardo Palma University. In addition, a statistically significant association between anxiety and depression was evidenced (p: 0.038). For this reason, it is recommended to implement a psychological accompaniment throughout the medical university career.